1994
DOI: 10.1108/eum0000000003989
|View full text |Cite
|
Sign up to set email alerts
|

Women in Non‐traditional Occupations

Abstract: Discusses a recently completed research project on women in construction management occupations. Focuses on the issues generated by the research and main conclusions. The methodology is briefly discussed and the sequence of the investigation outlined. Presents the problem of the under‐representation of women in the construction industry with statistical evidence. Issues raised include the image of the construction industry, knowledge as a determinant of career choice and organizational culture. States conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 7 publications
(7 reference statements)
6
79
0
1
Order By: Relevance
“…Research has tried to investigate why this is the case and why some women choose a discipline that seems to be in opposition to, or at least have some friction with, their sex. It has been found that the decision to study engineering is influenced by interests and ability, knowledge of the subject (Gale, 1994), the chance to gain hands-on experience (Madhill et al, 2007;Woolnough, 1994) and 'contact' with engineering (Cockburn, 1985 (Cockburn, 1985), supportive parents (Godfroy-Genin's, 2009); and personality -self image and gender identity, motivations (Alpay et al, 2008;Evetts, 1998;López Sáez, 1994) or 'acts of rebellion' (Carter and Kirkup, 1990: 40-41). It has also been found in research that perceptions about engineering can have an impact on whether a young adult will decide to study engineering once they have achieved success at school level (Phipps, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Research has tried to investigate why this is the case and why some women choose a discipline that seems to be in opposition to, or at least have some friction with, their sex. It has been found that the decision to study engineering is influenced by interests and ability, knowledge of the subject (Gale, 1994), the chance to gain hands-on experience (Madhill et al, 2007;Woolnough, 1994) and 'contact' with engineering (Cockburn, 1985 (Cockburn, 1985), supportive parents (Godfroy-Genin's, 2009); and personality -self image and gender identity, motivations (Alpay et al, 2008;Evetts, 1998;López Sáez, 1994) or 'acts of rebellion' (Carter and Kirkup, 1990: 40-41). It has also been found in research that perceptions about engineering can have an impact on whether a young adult will decide to study engineering once they have achieved success at school level (Phipps, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Extant research has not explored the role of cultural-cognitive elements at the industry level as an influence on the gender composition of corporate boards. However, the established link between corporate boards, culture and cognition (Laurila and Ropponen, 2003;Ocasio, 1999) and the impact culture has on women's position in a given industry (Gale, 1994;Miller, 2004;French and Strachen, 2007) suggests research at the juncture between board demography, gender and industry culture may potentially offer beneficial insights into understanding industry wide patterns of female corporate board representation.…”
Section: Proposition 4: Industries Where the State Is A Shareholder Wmentioning
confidence: 99%
“…In such a maledominant environment, women engineers are easily neglected by construction managers or organizations. It is widely acknowledged that construction is one of the industries where professional women are under-represented (Dainty et al, 2000a, b;Fielden et al, 2000, Gale, 1994. A lack of information from the perspectives of both men and women engineers and inadequate separate studies of men engineers and women engineers lead to ill-informed judgments about the latter"s managerial skills in many developing countries, Thailand being no exception.…”
Section: Introductionmentioning
confidence: 99%